Far Lateral Transcondylar Transtubercular Approach for Microsurgical Resection of Foramen Magnum Meningioma: Operative Video and Technical Nuances - Liu, James K.; Dodson, Vincent N.; Meybodi, Ali T. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Surgical access to the ventral foramen magnum remains a technical challenge. With large lesions in this region compressing the brainstem and distorting the regional neurovascular relationships, formulating a surgical plan and its appropriate execution have crucial importance in achieving favorable outcomes. While the endoscopic endonasal approaches have gained increasing attention to access the clivus and the ventral brainstem, foramen magnum meningiomas are still preferred to be removed via an approach that obviates a trajectory through the nasopharyngeal mucosa. Therefore, the far lateral approach remains one of the most practical approaches for these challenging lesions. This operative video demonstrates the use of the far lateral transcondylar transtubercular approach to remove a large meningioma in the ventral foramen magnum in a 63-year-old male with progressive cervical myelopathy, presenting as spastic quadriparesis without any cranial nerve abnormality. Using a right-sided far lateral transcondylar transtubercular approach, the meningioma was exposed within the cerebellomedullary gutter engulfing the vertebral artery and distorting the course of the adjacent cranial nerves. Using the different corridors identified between the vertebral artery, spinal accessory, vagus, and hypoglossal nerves, multiple angles of attacks to the tumor were established and utilized to resect the lesion. A gross total resection was achieved and the patient was neurologically intact without any neurological deficits. This video demonstrates the importance of understanding the intricacies of neurovascular anatomy of the cervicomedullary region (i.e., the various triangles formed between these structures), and the effective use of these corridors to safely and efficiently remove a challenging ventral foramen magnum meningioma with neurovascular involvement, while preserving cranial nerve function. The surgical technique and nuances are described in a step-by-step fashion in this illustrative operative video.The link to the video can be found at: https://youtu.be/s1dFhuaRSt8.
Keywords: far lateral approach; transcondylar transtubercular; foramen magnum meningioma; skull base surgery